Human-Centered Design and Development of an Adjustable Crutch: Enhancing Usability and Functionality for Physical Disabilities - Lingkon, Md. Limonur Rahman; Paul, Rahul Chandra; Sarfaraj, Nagib Md.; Fahad, Fazle Rabbani; Hossain, Md. Aliwar (International Journal of Integrated Engineering, 2025)
Crutches are becoming more and more critical as the number of physically disabled individuals in a nation rises. The need for multidimensional and multivariate crutches to assist people with disabilities is more significant today. Before making a variant of the standard crutch, a proper study must be done to construct a stable crutch for high load-carrying capacity. Additionally, various crutch models are also available. A new challenge is the development of an entirely new crutch model. Numerous types of analysis were carried out in this research to create a reliable and effective product, including market analysis, quality function deployment, functional structure development, Kano model development, specification and design analysis, materials and manufacturing processes, and cost analysis. All facets of product development, such as consumer requirements, assembly schematics, and recycling practices, were explored in the study. The most intriguing additions were the product’s capacity to fold and the seating tool facility. A load analysis was conducted to meet this requirement, utilizing data from a survey of disabled persons employed in the business regarding the equipment required for people with physical challenges, especially when selecting materials. Another unique feature of our product is an adjustment system that helps the user to adjust its height. These features are new and thus make our product more memorable compared to existing products on the market. Ultimately, the product was developed and utilized successfully through the research.